0
$\begingroup$

I need to find the inverse Laplace transform of $F(s) = \frac{2s}{s^{4}+s^{2}+1}.$

I realise that I need to do something with the denominator so I can convert to partial fractions, but I am not able to do so. Any help will be appreciated, thanks!

$\endgroup$
4
$\begingroup$

HINT:

$$s^4+s^2+1=(s^2+1)^2-s^2=\cdots$$

$$\implies2s=s^2+s+1-(s^2-s+1)$$

$\endgroup$
1
$\begingroup$

Since: $$\mathcal{L}^{-1}\left(\frac{s}{s^2-a^2}\right)=\cosh(at),\qquad\mathcal{L}^{-1}\left(\frac{a}{s^2+a^2}\right)=\sin(at)\tag{1}$$ and: $$\frac{2s}{s^4+s^2+1} = \frac{1}{s^2-s+1}-\frac{1}{s^2+s+1}\tag{2}$$ it follows that: $$\mathcal{L}^{-1}(F(s)) = \color{red}{\frac{4}{\sqrt{3}}\cdot\sinh\left(\frac{t}{2}\right)\cdot\sin\left(\frac{\sqrt{3}}{2}t\right)}.\tag{3}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.